Relationship between cell envelope ultrastructure and the antibacterial properties of a novel hydrophobic eumelanin-inspired derivative - Reed, Daniel R.; Nehmzow, Katherine; Essandoh, Martha A.; Ebqa'ai, Mohammad A.; Nelson, Toby L.; Lutter, Erika I.; Cook, Gabriel A.; Champlin, Franklin R. (Frontiers in Bacteriology, 2023)
Introduction Unique impermeability properties of the gram-negative outer cell envelope typically render these organisms intrinsically resistant to hydrophobic antibacterial compounds. Eumelanin-inspired indoylenephenyleneethynylene (EIPE) compounds possess scaffolding to which functional groups were attached to potentially provide antibacterial properties in the forms of hydrophilic (EIPE-HCl) and hydrophobic (EIPE-1) derivatives. Methods Standardized disk agar diffusion and microbroth dilution bioassays were employed to assess the susceptibility of disparate gram-negative and gram-positive bacterial pathogens to the two compounds. EIPE-1 mechanisms of action and intrinsic resistance were further investigated turbidimetrically in batch cultures with the aid of the gram-negative outer membrane permeabilizer compound 48/80. Results Hydrophobic derivative EIPE-1 exhibited a gram-positive antibacterial spectrum, while hydrophilic derivative EIPE-HCl possessed no antibacterial properties. EIPE-1 exhibited minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values below 2.0 µg/mL against all gram-positive bacteria, including two methicillin-resistant strains. In contrast, MIC/MBC values greater than 128 µg/mL were obtained for all gram-negative bacteria examined. Susceptibility of two strains of the strict anaerobe Clostridioides difficile indicated the EIPE-1 mechanism of action does not require molecular oxygen. Turbidimetric growth curves revealed EIPE-1 induced rapid bacteriolysis of Bacillus subtilis ATCC 6633, thereby suggesting a membrane-directed modality. Lastly, the outer membrane permeabilizer compound 48/80 failed to markedly sensitize any of three phylogenetically disparate gram-negative organisms to EIPE-1. Conclusion These data suggest that the hydrophobic melanin-inspired derivative EIPE-1 inhibits gram-positive bacteria in a cytoplasmic membrane-directed manner independent of oxygen. Moreover, a secondary mechanism may function concomitantly with outer membrane exclusionary properties to underly the intrinsic resistance of gram-negative pathogens.